Exploring Power Distance in Organizations Undergoing Agile Transformations - Mattos, Claudio Saraiva; Dutra, Eliezer; Santos, Gleison (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2025)
Power distance is defined as the degree to which members of a society expect and accept the unequal distribution of power among people. In organizations undergoing agile transformation, high power distance can result in restricted communication, reduced collaboration, and resistance to change—factors that can negatively impact software quality. However, identifying latent behaviors associated with this high power distance is not always straightforward. This paper presents how the Instrument for Diagnosing Power Distance (IDPD) was developed and evaluated in an industrial setting. The research method adopted was Design Science Research (DSR) and followed guidelines for the development of psychometric scales. The IDPD’s measurement items are based on manifestations of power distance related to human factors, elements of organizational culture, and process-related aspects identified through a systematic literature review. The instrument was preliminary evaluated by a panel of experts, applied in a case study with two agile organizations, and validated through a survey. The experts considered the IDPD items to be clear, relevant, and adequate for measuring power distance in agile contexts. The case study diagnosis indicated that high power distance had little to no effect on elements of organizational culture and human factors. However, process execution and improvement may be affected by high power distance. The participants considered the results relevant and indicated their intention for future use of the IDPD. The survey preliminarily showed good psychometric indices. Initial evidence suggests that the IDPD can be used to diagnose power distance in agile organizations or organizations undergoing agile transformation.